Pengembangan Media Pembelajaran Lapbook dengan Flashcard dan Q&A Card untuk Meningkatkan Hasil Belajar pada Mata Pelajaran IPAS "Harmoni dalam Ekosistem" Kelas V Sekolah Dasar - Karini, Vinanda Syafara; Fathurrahman, Moh. (Paedagogie, 2026)
IPAS learning in elementary schools requires innovative and engaging learning media to encourage student involvement and improve learning outcomes. One alternative learning medium is a Lapbook combined with flashcards and barcode-based QnA cards. This study aims to develop a Lapbook learning media integrated with flashcards and QnA cards on the IPAS topic Harmony in Ecosystems and to determine its feasibility and effectiveness in improving learning outcomes of fifth-grade students at SD Negeri Sukolilo 03. This study employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, expert validation questionnaires, pre-test and post-test assessments, and student response questionnaires. Data analysis was conducted using descriptive qualitative and quantitative methods, including normality tests, paired sample t-tests, and N-Gain analysis. The results showed that the developed Lapbook learning media was categorized as very valid by material experts and valid by media experts. Effectiveness testing indicated a significant improvement in student learning outcomes, with a significance value of < 0.05 and an N-Gain score of 0.7641 in the high category. Therefore, the Lapbook learning media combined with flashcards and QnA cards is feasible and effective as an innovative learning alternative for IPAS learning on the topic of Harmony in Ecosystems for fifth-grade elementary school students.